Enzyme assays on GPx and SOD in alloxan-induced diabetic mice given yellow velvet leaf (Limnocharis flava) extracts - Yithro Serang; Metrikana Novembrina; Henry Setiawan Haryanto; Siti Erni Saputri (Pharmaciana, 2020)
In a pathological condition such as diabetes, the increase of oxidative stress may decrease endogenous antioxidant activities, so the body cannot detoxify free radicals and prevent cell damage. The yellow velvet leaf is one of the natural antioxidant sources. This research investigates anti-hyperglycemic activities of ethanol extracts from yellow velvet leaves and SOD and GPx activities, the antioxidant enzymes. This experimental laboratory research used a posttest only group design. This research subjects were 25 alloxan-induced white male rats of Wistar strains conditioned as the type 2 Diabetes Mellitus (DM). The rats were clustered into five groups: the group I was the no-treatment control group, the group II was the positive control group given glibenclamide 0.45 mg/kg BW(rat's body weight) as the treatment, and group III, IV, and V were the experimental groups treated with yellow velvet leaf ethanol extracts with the doses of 32.5 mg/kg BW, 65 mg/kg BW and 130 mg/kg BW respectively. The activity tests of SOD and GPx, furthermore, were conducted. The results revealed that the dose of 130 mg was the most effective in increasing SOD and GPx activities. The increase of SOD and GPx levels also influenced the blood glucose level, which decreased significantly on 130mg. When the blood sugar level decreases, the stress oxidative itself can be reduced, increasing the endogenous antioxidant activities. It was concluded that the ethanol extract of yellow velvet leaf (Limnocharis flava) on the dose of 130mg/kg BW has a significant influence on SOD and GPx activities in alloxan-induced diabetic RA, and not significantly different from glibenclamide